Icariin ameliorates lung injury in severe acute pancreatitis of rat models - GU Wen-hao, GUO Fei-xia,XU Yu-peng, LU Xin-yu, HU Qing-qing (Jichu yixue yu linchuang, 2022)
Objective To evaluate the protective effect and inflammation inhibition mechanism of icariin (ICA) on lung injury in rat model with severe acute pancreatitis (SAP). Methods The rats were randomly divided into sham operation group (sham group), model group (SAP group, 5% sodium taurocholate was retrograde pumped into bile duct according to 0.1 mL/kg through micropump) and experimental group (ICA group, icariin 80 mg/kg intervention was given 2 hours before modeling). There were 6 rats in each group. Twenty-four hours after the establishment of the model, the inferior vena cava blood, pancreatic tissue and lung tissue were collected. The pathological injury of pancreas and lung was observed by HE staining; The activity of amylase, serum IL-6, IL-1β and TNF-α were measured by ELISA; The expression of inflammatory factors IL-6, IL-1β and TNF-α in lung tissue was determined by immunohistochemical staining; And the ratio of phosphorylated JNK/JNK to phosphorylated NF-κB/NF-κB in lung tissue was measured by Western blot. Results The pathological scores of pancreas and lung in SAP group were significantly higher than those in sham group; And the pathological scores of pancreas and lung in ICA group were significantly lower than those in SAP group. Serum amylase activity, serum IL-6, IL-1β and TNF-α content and the expression of IL-6, IL-1β and TNF-α in lung tissue in SAP group were significantly higher than those in sham group; While serum amylase activity, serum IL-6, IL-1β and TNF-α content and the expression of IL-6, IL-1β and TNF-α in lung tissue in ICA group were significantly lower than those in SAP group. The level of phosphorylated JNK and phosphorylated NF-κB in lung tissue of SAP group were significantly higher than those of sham group; While icariin might significantly reduce the level of phosphorylated JNK and phosphorylated NF-κB in lung tissue. Conclusions ICA ameliorates lung injury in SAP rat model by inhibiting acute inflammation response,which is potentially mediated by JNK/NF-κB signal pathway.